2017
DOI: 10.1186/s12894-016-0190-2
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral benign renal oncocytomas and the role of renal biopsy: single institution review

Abstract: BackgroundThe goal was to assess the natural history and management of patients with pathologically proven bilateral (synchronous) RO after undergoing initial partial nephrectomy (PN).MethodsAll patients underwent either robotic/laparoscopic or open PN by two experienced genitourinary oncologists from 2005–2013. Final pathology was determined by surgical excision, CT-guided percutaneous core biopsy (CT-biopsy) or fine needle aspiration (FNA). Patient demographics, tumor characteristics (pathologic data, locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Certain types of renal tumors, such as oncocytoma, may be very challenging to differentiate from malignant renal masses [ 7 ]. As any surgical intervention to remove a renal mass appropriately will worsen renal function to some degree, understanding if bilateral renal surgical manipulation is truly warranted prior to time of surgery is a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Certain types of renal tumors, such as oncocytoma, may be very challenging to differentiate from malignant renal masses [ 7 ]. As any surgical intervention to remove a renal mass appropriately will worsen renal function to some degree, understanding if bilateral renal surgical manipulation is truly warranted prior to time of surgery is a priority.…”
Section: Discussionmentioning
confidence: 99%
“…The patient could have undergone a confirmatory biopsy of the contralateral right renal mass with AS imaging protocols instead of undergoing a right PN [ 13 ]. PNs are associated with complications such as postoperative hemorrhage and urine leak, such that for every 1 cm increase in tumor diameter, the risk of postoperative hemorrhage increases by 45% [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant proportion of small renal masses (SRMs) are benign, with oncocytoma being the most frequent benign contrast-enhancing renal mass found. A well-known problem faced by pathologists is differentiating oncocytomas from chromophobe RCC [ 56 , 57 , 58 ]. Zhu et al reported favorable results in RCC subtyping in surgical resection and RMB specimens, as well as promising results in oncocytoma diagnosis in RMB [ 59 ].…”
Section: Artificial Intelligence Aided Diagnosis Of Rcc Subtypesmentioning
confidence: 99%